Response of Soil Nematodes Under Different Pest Management Practices: A Field Experimental Approach in Tomato (Lycopersicon Esculentum L.) Growing Agro-Ecosystem - Gupta, Dipak; Bhusal, Daya Ram (Journal of Institute of Science and Technology, 2018)
The need of eco-friendly pest management practice is important to maintain soil biodiversity and sustainable agriculture. Therefore rigorous investigation is needed for the environmentally friendly pest management techniques worldwide including Nepalese Tomato growing farms. We conducted field experiment to monitor the diversity and community structure of soil nematodes under different pest management practices in Tomato (Lycopersicon esculentum) growing farm. The study was conducted during summer and winter season in 2015 in Tokha area of Northern part of Kathmandu valley. The field was designed as Urine mixture plot (MP), Pesticides plot (PP), Botanicals plots (BP) and Control plot (CP). Our result indicated the variation of abundance and diversity of nemato-fauna with treatment plots and seasons. The generic diversity and community composition of nematodes in Urine mixture treating plots (MP) was increased significantly whereas decreased in pesticide applying plot (PP). The F/B ratio was significantly affected with treatment system rather than seasonality and found to be increased in pesticides applying plots. The abundance samples of nematodes genera were well separated in our discriminate ordination. We highlight the need of further exploration on the diversity and community dynamics of soil nematodes under different pest management practices in Tomato growing Nepalese agro-farms for sustainable soil ecosystem service. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 45-55